Peran Maktab Dakwah wa al-Jaliyat dalam Meningkatkan Keterampilan Bahasa Arab Warga Negara Indonesia di Kota al-Kharj, Arab Saudi: The Role of Maktab Dakwah wa al-Jaliyat in Enhancing Arabic Language Proficiency Among Indonesian Citizens in al-Kharj City, Saudi Arabia - Rachmat Bin Badani Tempo; Ahmad Noor Fauzie (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
This Community Service Program (PkM) aims to improve Arabic language skills among Indonesian citizens living in al-Kharj City, Saudi Arabia, through Maktab Dakwah wa Al-Jaliyat. The implementation of PkM is carried out by evaluating the effectiveness of the program in facilitating Indonesian citizens to deepen their understanding of Islam through mastering the Arabic language. The activity began by analyzing the implementation of the program, the challenges faced, and the role of Maktab Dakwah wa Al-Jaliyat as the organizing organization. The results of the activities show that this program has had a positive impact in increasing mastery of the Arabic language and understanding of Islamic sources. However, there are obstacles such as differences in participant abilities and the need for curriculum adjustments. This program concludes the important role of Maktab Dakwah wa Al-Jaliyat in providing an effective learning platform and developing cross-institutional collaboration to increase the effectiveness of the program in the future.